Explicit and Implicit Belief-Based Gender Discrimination: A Hiring Experiment - Barron, Kai; Ditlmann, Ruth; Gehrig, Stefan; Schweighofer-Kodritsch, Sebastian (Management Science, 2025)
This paper studies a key element of discrimination, namely, when stereotypes translate into discriminatory actions. Using a hiring experiment, we rule out taste-based discrimination by design and test for the presence of two types of belief-based gender discrimination. We document evidence of explicit discriminators—individuals who are willing to discriminate even when their hiring choices are highly revealing of their gender-biased beliefs. Crucially, we also identify implicit discriminators—individuals who do not discriminate against women when taking a discriminatory action is highly revealing of their biased beliefs, but do discriminate against women when their biased motive is obscured. Our analysis highlights the central role played by features of the choice environment in determining whether and how discrimination will manifest. We conclude by discussing the implications for policy design. This paper was accepted by Marie Claire Villeval, behavioral economics and decision analysis. Funding: K. Barron and S. Schweighofer-Kodritsch gratefully acknowledge financial support from the Deutsche Forschungsgemeinschaft through CRC TRR 190 [Grant 280092119]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.01229 .